Analysis of Customer Data Processing Management Applications at Yuzaka Printing Palembang - Nasri, Irian; Hendriansyah; Triana, Dora Indah (Maroon Journal De Management, 2024)
This research aims to analyze the needs and implementation of customer data processing management applications at Yuzaka Printing Palembang. This application is designed to increase operational efficiency and accuracy in managing customer data, which includes order recording, transaction history, and customer relationship management. The research method used involves collecting data through direct observation, interviews with management, and analysis of company documents. The results of the analysis show that the manual system used previously often resulted in data errors, delays in order processing, and a lack of information integration between operations and management. By implementing technology-based data management applications, Yuzaka Printing can minimize the risk of errors, improve customer service, and support more timely decision making. This application includes main features such as customer database management, order status tracking, notification system for pickup schedules, and automatic financial reports. Implementation of this system is expected to not only increase productivity, but also build better long-term relationships with customers.